Pengaruh Current Ratio, Price Earning Ratio, Net Profit Margin, Total Assets Turnover dan Debt to Equity Ratio Terhadap Return Saham - Mahirun, Mahirun; Ana, Firda Rizqi; Jannati, Arih (Universitas Sang Bumi Ruwa Jurai, 2024)
Our research aims to test and analyze the effect of current ratio, price earning ratio, net profit margin, total asset turnover, and debt to equity ratio on stock returns in banking companies on the Indonesia Stock Exchange for the period 2017-2021. The analytical tool used is multiple linear regression with the help of SPPS software. The main findings of the research net profit margin affects the company's stock return positively and significantly and the debt to equity ratio which is an indicator of debt policy has a significant negative effect on stock returns. While the price earning ratio as an investment opportunity, although the effect is positive but not significant. Other findings of our research current ratio and total assets turnover turned out to have a negative effect, although not significant.